Extraction of river networks from digital elevation model for the Rompin river basin - Chong, Poi San (2018)
Mapping and topography visualization of an area of interest has become more convenient due to the advancement of technology in the geographical information system (GIS). The advancement in the mapping technology is enhanced by the increasing availability of the Digital Elevation Model (DEM) also known as the digital spatial data provider. The hydrological features of a basin extracted from the DEM is precise and can be done faster compared to the traditional method. The purpose of this study are to delineate the river network and extract the physical hydrological characteristics from DEM dataset for the Rompin River Basin. Shuttle Radar Topography Mission digital elevation model (SRTM 1 Arc-Second Global Elevation Data) with 30 m resolution was used as the DEM for this study. The extraction of the physical characteristics required was performed by using ArcGIS application integrated with HEC-GeoHMS extension. For the validation of the simulated river network, the results obtained were compared with the digitized river network from Google Earth. Based on the validation outcome, it is concluded that DEM of 30 m is sufficient to delineate and estimate the river network and physical characteristics of the Rompin River Basin with acceptable precision.